Io sono Salvo works and writings 1961-2015 - Salvo 1947-2015; Nickas, Robert; Volpato, Elena (NERO, 2023)
"Io sono Salvo" is a monograph conceived as a self-portrait: a story of the artist’s practice through his works and words. A collection of writings, including the treatise On Painting, unpublished texts, and various interviews given over the years, complements a vast selection of his works, presented in chronological sequence
Keywords: Salvo -- 1947-2015; Bildband